(untitled) (Homoeopathy for All, 2023)
The last few years have shown us a phase of a difficult pandemic called Covid. Observing the ongoing situation, it is difficult to say whether the pandemic has even ended! Covid-19 is caused by the SARS-CoV-2 virus. Affecting the respiratory organs at large, it produces symptoms like cold, flu, pneumonia, breathlessness, etc. Even after the pandemic receded, patients reportedly suffered from respiratory troubles in the post-covid phase. Out of all these symptoms, cough is one of the most common manifestations of post-covid syndrome. When this particular cough is acute in nature, it is easy to cure and is self-limited. However, the cough becoming chronic in nature (lasting for more than 8 weeks) is the real struggle. These days, physicians treating patients with persisting coughs obtain a history of the pandemic associated with the recurrence of cough. The patient complaints of not being well ever since being down with the attack of Covid. This is what a homeopath may link as the – ‘Never well since syndrome’. As the patients stopped responding to the frequently used medications, homeopathy can offer a number of choices for the same. With the help of homeopathic medicines, the intensity and duration of cough can be reduced to a remarkable effect without leading to any adverse effects. This article focuses on the various homeopathic remedies that can be used to alleviate persisting cough inhibiting its recurrence.